2018
DOI: 10.1002/anie.201802242
|View full text |Cite
|
Sign up to set email alerts
|

Simple Synthesis of Functionalized 2‐Phosphanaphthalenes

Abstract: A simple synthesis of sodium 2-phosphanaphthalene-3-olate (1) based on the extrusion of N from phthalazine using Na[OCP] is reported. This heterocycle can be readily functionalized at the negatively charged oxygen center using a variety of electrophilic substrates. The coordination chemistry of both 1 and its neutral derivatives was explored, revealing their facile use as P-donor ligands for late-transition-metal complexes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 66 publications
2
19
0
2
Order By: Relevance
“…[74] This compound can be easily further derivatized using arange of electrophiles such as ClP(O)Ph 2 or 2-chloropyridine.T he resulting neutral compounds can be used as new chelating ligands.Inaclosely related reaction, Caulton and co-workers have shown that tetrazines react readily with Na(OCP) under elimination of N 2 whereby various 1,2,4-diazaphosphinin-5olates are obtained as products. [74] This compound can be easily further derivatized using arange of electrophiles such as ClP(O)Ph 2 or 2-chloropyridine.T he resulting neutral compounds can be used as new chelating ligands.Inaclosely related reaction, Caulton and co-workers have shown that tetrazines react readily with Na(OCP) under elimination of N 2 whereby various 1,2,4-diazaphosphinin-5olates are obtained as products.…”
Section: Six-membered Heterocyclesmentioning
confidence: 99%
“…[74] This compound can be easily further derivatized using arange of electrophiles such as ClP(O)Ph 2 or 2-chloropyridine.T he resulting neutral compounds can be used as new chelating ligands.Inaclosely related reaction, Caulton and co-workers have shown that tetrazines react readily with Na(OCP) under elimination of N 2 whereby various 1,2,4-diazaphosphinin-5olates are obtained as products. [74] This compound can be easily further derivatized using arange of electrophiles such as ClP(O)Ph 2 or 2-chloropyridine.T he resulting neutral compounds can be used as new chelating ligands.Inaclosely related reaction, Caulton and co-workers have shown that tetrazines react readily with Na(OCP) under elimination of N 2 whereby various 1,2,4-diazaphosphinin-5olates are obtained as products.…”
Section: Six-membered Heterocyclesmentioning
confidence: 99%
“…[4a] Although the phosphanaphthalenes were first synthesized in the 1970s, they have recently re‐captured the attention of the scientific community. As a result, for instance, new synthetic strategies to fuse phosphanaphthalenes with oxazole rings and the improvement of their synthesis have been developed. In the following sections, we will particularly focus on larger linearly fused systems containing six‐membered phosphorus heterocycles.…”
Section: Phosphorus Heteroarenes: the Originmentioning
confidence: 99%
“…Note, during the preparation of this manuscript, Grützmacher et al. reported one example of a phosphanaphthalene through N 2 elimination; however, the synthesis requires reaction times over several weeks to months at 80 °C . For accessing azaphosphinines, triazines and tetrazines should be ideal starting materials as they are electron‐deficient, known to undergo inverse‐electron‐demand hetero‐D.A.…”
Section: Figurementioning
confidence: 99%